Analysis and countermeasure to improve overall equipment effectiveness (OEE) on chassis line at Tan Chong Industry - Nur Syahirah, Ismail (2016)
Overall Equipment Effectiveness (OEE) is a powerful metric of manufacturing performance incorporating measures of the utilization, yield and efficiency of a given process, machine or manufacturing line. When associated with the reasons for performance loss, OEE provides the means to compare and priorities improvement efforts. This project assesses the current condition of Chassis-Final Assembly lines of Nissan Tan Chong Motor Assemblies Sdn Bhd, a company of car manufacturer in order to reduce unplanned downtime due to line stoppages to maximize the productivity. Before obtaining the data to calculate the existing OEE value, the product or process that have the highest downtime rate need to be identified at Chassis-Final Assembly Department. The methods used to analyze these various causes were control chart to find the out of control point, Pareto Analysis to find the critical problem, Ishikawa diagram to find causes affecting the problem, and 5W1H to proposed the recommendation. After knowing the causes of various activities that leads to high downtime rate, then recommendations for OEE improvements are 84.35% and 84.31% for A, and B shift respectively. From the existing to world class ranking OEE there are improved by 4.51% and 4.71% for A, and B shift respectively, that could be used by Nissan Tan Chong Motor Assemblies Sdn Bhd were ready to be made.